2019
DOI: 10.1021/acs.langmuir.9b01821
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Rheology of Gallium-Based Liquid Metals

Abstract: Gallium and its alloys react with oxygen to form a native oxide that encapsulates the liquid metal with a solid "skin". The viscoelasticity of this skin is leveraged in applications such as soft electronics, 3D printing, and components for microfluidic devices. In these applications, rheological characterization of the oxide skin is paramount for understanding and controlling liquid metals. Here, we provide a direct comparison of the viscoelastic properties for gallium-based liquid metals and illustrate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 42 publications
4
74
0
Order By: Relevance
“…Furthermore, we could not mix large particles when they had hierarchical surface features; mesoporous silica and activated alumina with particle sizes up to 200 m were nonmixable; however, regular, nonporous powdered silica is mixable. We It has been observed that when the volume of liquid gallium is small, the behavior of the oxide skin dominates the rheological properties (5,40), showing viscoelastic behavior with a high yield stress (41). We thus propose that GalPs form as shown schematically in figs.…”
Section: Resultsmentioning
confidence: 85%
“…Furthermore, we could not mix large particles when they had hierarchical surface features; mesoporous silica and activated alumina with particle sizes up to 200 m were nonmixable; however, regular, nonporous powdered silica is mixable. We It has been observed that when the volume of liquid gallium is small, the behavior of the oxide skin dominates the rheological properties (5,40), showing viscoelastic behavior with a high yield stress (41). We thus propose that GalPs form as shown schematically in figs.…”
Section: Resultsmentioning
confidence: 85%
“…It also avoids the need for shear when printing from a nozzle. As noted previously, liquid metals are low viscosity fluids, having a viscosity on the order of ≈2mPa s. [24,26,81] This should let them be easily aerosolized or jetted, however the extremely large surface tension and presence of a surface oxide complicate using liquid metal in droplet dispensing systems. In brief, it limits the nozzle size.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, this behavior is seen with mercury, which does not rapidly form a native surface oxide, [24] or with EGaIn if the oxide layer is removed. [25] The oxide skin will yield beyond a critical surface stress (≈0.3-0.5 N m −1 ) [5,24,26,27] but otherwise is stable and prevents the metal from flowing in a way that increases area. Similar to surface tension, the pressure required to rupture the surface is simply the critical surface stress multiplied by the curvature of the surface (2/R in the case of a spherical drop, where R is the radius of the drop).…”
Section: Liquid Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[319][320][321] Liquid metals usually have high surface tensions, and an oxide layer occurs on the surface of liquid metal droplets once it is exposed to air. [322,323] DIW and spray coating have been applied to deposit liquid metal electrodes. [324][325][326][327][328][329][330] In addition to the noncontact methods, liquid metal can also be patterned by the contact method.…”
Section: Metal-based Nanomaterialsmentioning
confidence: 99%